A Brief Exit Before a Grand Entrance - MacDonald, Kathy; Fraser, Marina; Madore, Yvonne (Operating Room Nurses Association of Canada Journal, 2018)
Churchill has been quoted as stating “He who fails to plan, plans to fail.” Significant planning and collaboration were necessary to prepare for the first Ex-utero Intrapartum Treatment (EXIT) procedure in the IWK Health Centre in Halifax, NS. EXIT is a life-saving technique used to secure a fetal airway when there is some type of airway compression involved. The procedure is done while oxygenation and perfusion are maintained through utero-placental circulation} The IWK’s obstetrical team followed a mother whose fetus was diagnosed in utero with a high airway anomaly/obstruction.